The change in cholesterol content of long chain fatty acid egg during processing and its influence to the Rattus norvegicus L. blood cholesterol content - Dini Hardini; Tri Yuwanta; Zuprizal .; Supadmo . (Indonesian Center for Animal Research and Development (ICARD), 2006)
Egg containing long chain unsaturated fatty acids is a functional food, because it is highly nutritious and could prevent diseases, (omega 3 and 6) such as coronary heart attack. The research was aimed to measure the change of egg cholesterol content during proceesing: frying, oiless frying and boiling and their influence to the blood plasma cholesterol of normal and hypercholesterolemia rat. Seven treatments of egg yolk were frying at 170°C for 3 min (welldone = GM), and 1min (half medium fried = GSM) using deep fryer , oilless frying at 70°C for10 min (fried = TM), and 6 min (half fried = TSM) using Teflon pan, and boiling at 100°C for 10’ (boiled = RM) dan 4 min (half boiled = RSM) using pan provided with thermoregulator and a fresh omega egg as a control. The Completely randomized design was apllied for 4 weeks research period. The data from different treatments were analyzed by Orthogonal Contrast. Fifty 2 months old male rats Rattus norvegicus L. separated in 2 groups; normal and hypercholesterolemia (blood cholesterol > 200 mg dl-1). The rats were placed in individual cage, fed 15 g h-1 day-1 and water drinking ad libitum. The ration was composed of 90% basal commercial feed BR II and 10% egg yolk was given to each animal at 20% of live weight. Factorial 2 x 7 of completely randomized design was applied. The data were analyzed by ANOVA and Duncan’s Multiple Range Test. Processsing method of egg affected to cholesterol content of egg, The lowest and the highest cholesterol contents were observed in TSM (0.30 g/100g) and GM (0.37 g/100g), respectively. Biological test using Rattus norvegicus L rat showed that either fresh and processed long chain fatty acid egg decreased plasma cholesterol. The highest and the lowest decreases of cholesterol content were found in the group consumed RSM (8.64%) and GM (1.77%) for normal rat; and control (46.3%) followed by RSM (44.53%) and GM (24.86%), respectively. To maintain normal cholesterol and decrease cholesterol content of cholesterolemian, the omega egg should be consumed in fresh or half boiled egg. Key Words: Cholesterol, Omega-3, Omega-6, Rattus norvegicus L.